2006
DOI: 10.1103/physreve.73.036213
|View full text |Cite
|
Sign up to set email alerts
|

Experimental synchronization of spatiotemporal chaos in nonlinear optics

Abstract: We demonstrate that a unidirectional coupling between a pattern forming system and its replica induces complete synchronization of the slave to the master system onto a spatiotemporal chaotic state.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The study of chaotic synchronization in the spatially extended systems was experimentally an theoretically carried out for the nonlinear optical [31][32][33] and chemical [34] systems and for the low-frequency oscillations in plasma discharge tubes [35,36]. It was shown that while introducing the unidirectional or symmetric coupling in the distributed systems they demonstrate the various types of chaotic synchronization, namely the complete, lag and generalized synchronization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of chaotic synchronization in the spatially extended systems was experimentally an theoretically carried out for the nonlinear optical [31][32][33] and chemical [34] systems and for the low-frequency oscillations in plasma discharge tubes [35,36]. It was shown that while introducing the unidirectional or symmetric coupling in the distributed systems they demonstrate the various types of chaotic synchronization, namely the complete, lag and generalized synchronization.…”
Section: Introductionmentioning
confidence: 99%
“…Most research dealing with chaotic synchronization were realized for the systems with low number of degrees of freedom [2][3][4]14] and for the sample models of spatially extended systems (chains and networks of coupled nonlinear chaotic oscillators [3,[25][26][27], coupled Ginsburg-Landau [3,28,29] and Kuramoto-Sivashinsky [30] equations and others). The study of chaotic synchronization in the spatially extended systems was experimentally an theoretically carried out for the nonlinear optical [31][32][33] and chemical [34] systems and for the low-frequency oscillations in plasma discharge tubes [35,36]. It was shown that while introducing the unidirectional or symmetric coupling in the distributed systems they demonstrate the various types of chaotic synchronization, namely the complete, lag and generalized synchronization.…”
Section: Introductionmentioning
confidence: 99%